Integrasi Interkoneksi Pendidikan Agama Islam dan Ekstrakurikuler Pramuka dalam Membentuk Kepribadian Siswa - Ruhama’, Ulfatur (JOIES (Journal of Islamic Education Studies), 2016)
This article is focused on the integration of Islamic education and scout as extra-curricular activities to build student`s character. This study reveals that interconnected integration between the subject of Islamic religious education in Junior High School (SMP) 4 Surabaya and SMP Khadijah 1 Surabaya runsvery well. Various factors that affect positively the implementation of this integration are the availability of infrastructure, the spirit of nationalism and moral development activities. While the inhibiting factors of interconnected integration between the subject of Islamic religious education and extracurricular scoutsat SMPN 4 and SMP Khadijah Surabaya deal with psychological aspect ofstudents who are quickly tired and lazy. The learners who are naughty and noisy often disturb the habituation of good character in learning process. Other inhibiting factors are infrastructures that are suddenly damaged or in use.